The Role of the Sabhara Unit Two-Wheel Patrol in Preventing the Crime of Theft During the Covid-19 Pandemic in the Bitung Police Legal Territory - Timothy Torro Ignatius Paskah Boseke (Advances in Police Science Research Journal, 2021)
The crime of theft is a crime that is in the spotlight in Bitung City. There is a very significant difference between the number of crimes of theft and other crimes. The Bitung Police Sabhara Unit, which holds the prevention function, is at the forefront of reducing the theft rate. The emergence of the Covid-19 pandemic resulted in Bitung City implementing restrictions on community activities. However, this does not reduce the number of criminal acts of theft. Therefore, the purpose of this study is to determine the role of the two-wheeled vehicle patrol of the Sabhara Unit in preventing criminal acts of theft during the Covid-19 Pandemic in the jurisdiction of the Bitung Police. This research is a field research using a qualitative approach. Theories used in this research include Role Theory, Management Theory and Routine Activity Theory. The focus of this research is on the two-wheeled vehicle patrol process carried out by the Bitung Police Satsabhara in preventing theft during the Covid-19 Pandemic. Primary data sources are taken from interviews with research subjects. Meanwhile, secondary data were taken from articles and research related to this research. The results of this study indicate that the two-wheeled patrol by Satsabhara experienced problems in the quantity and quality of personnel. It can be seen that some members of the Sabhara Unit do not yet have skills in Sabhara. A squad commander did not give directions before the start of the patrol. In terms of quantity, several personnel were assigned to the Covid-19 handling task force so that patrols were hampered. The patrols carried out have not been supported by the urban community. The method used is not effective because it only touches the main road area so that residential areas tend to be untouched. From this research, it is deemed necessary to improve the management process in the implementation of patrols, especially in the planning, organizing, mobilizing and monitoring sections. It is also necessary to pay attention to the man, money, method, materials, machine, and market factors.